Effect of synthesis temperature on characteristics of PNIPAM/alginate IPN hydrogel beads. Issue 15 (24th December 2014) - Ochi, Masanori; Ida, Junichi; Matsuyama, Tatsushi; Yamamoto, Hideo
ABSTRACT Poly(N‐isopropylacrylamide)/alginate interpenetrating polymer network hydrogel beads (IPN beads) were prepared via modified inverse emulsion polymerization, and the effect of the synthesis temperature on the characteristics of the IPN beads was investigated. Varying the synthesis temperature from 10 to 40°C led to slight differences in the FTIR and elemental analysis results, whereas significant differences in optical color, thermoresponsive behavior, and release properties of vitamin B12 were observed. The IPN beads prepared at low temperature were transparent and exhibited a large and drastic thermoresponsive volume change. On the other hand, the IPN beads prepared at high temperature were opaque and exhibited a small and gradual thermoresponsive volume change. In addition, the diffusion coefficient in the IPN beads prepared at 10°C decreased with increasing solution temperature, whereas the diffusion coefficient in IPN beads prepared at 40°C increased with increasing solution temperature. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41814.